ARCS Model-Based Educational Game for Athletics in Physical Education - Steven Roseily; Ketut Agustini; Ni Nyoman Parwati (Universitas Pendidikan Ganesha, 2025)
Physical Education, Sports, and Health (PJOK) learning, particularly in athletics, is often perceived as tedious and repetitive by students, leading to low learning motivation. This study aims to develop an educational game named